PACE Learning Model Based on Spring Media in Enhancing Mathematical Reasoning Skills - Robbi Fadlurrejas (Innovative Pedagogy and Education Studies, 2024)
This study aims to investigate the effectiveness of the PACE (Project, Activity, Cooperative, and Exercise) learning model based on Spring media in enhancing students’ mathematical reasoning skills. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The population consisted of secondary school students, with samples selected through purposive sampling and divided into an experimental group and a control group. Data were collected using a mathematical reasoning test designed to measure students’ abilities in logical thinking, pattern recognition, and problem-solving. The collected data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent sample t-test. The results indicate that students who were taught using the PACE learning model integrated with Spring-based media achieved significantly higher mathematical reasoning skills compared to students who received conventional instruction. These findings suggest that the integration of the PACE learning model with digital learning media is effective in improving students’ higher-order mathematical thinking skills and can serve as an alternative instructional strategy in mathematics education.